2012
DOI: 10.1007/s12603-012-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health related quality of life in older people with non-communicable diseases attending three primary care clinics in Malaysia

Abstract: Older people with non-communicable diseases were susceptible to lower health related quality of life. Increasing age, single, presence of co-morbid conditions, and poorer social support were predictors of lower physical health component of HRQoL. While the older women, Indian ethnicity and poorer social support reported lower mental health component of HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
2
25
0
6
Order By: Relevance
“…Despite their age, they maintain a healthy lifestyle by exercising regularly and doing recreational activities. In terms of support activity, older cancer patients also join cancer support groups to strengthen the social ties which significant in improving their general wellbeing (Sazlina et al, 2012). Our study suggests that older breast cancer survivors are aware of the importance of exercise in their daily lives to assist them in remaining cancer free (e.g exercising, recreational activity and having good relationships with family and friends).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Despite their age, they maintain a healthy lifestyle by exercising regularly and doing recreational activities. In terms of support activity, older cancer patients also join cancer support groups to strengthen the social ties which significant in improving their general wellbeing (Sazlina et al, 2012). Our study suggests that older breast cancer survivors are aware of the importance of exercise in their daily lives to assist them in remaining cancer free (e.g exercising, recreational activity and having good relationships with family and friends).…”
Section: Discussionmentioning
confidence: 78%
“…Social ties and religiosity have been shown to improve the psychological wellbeing of older people (Sazlina et al, 2012). A qualitative inquiry on 30 older women in the United States with breast cancer aged 67 to 90 also revealed that women were most likely to choose family members as their primary support person (Loerzel and Aroian, 2012).…”
Section: Older Women Breast Cancer Survivors: Decision Making Sourcementioning
confidence: 99%
“…A recent systematic review of 20 studies indicated that hypertensive patients had a lower QOL compared with normotensive people [7]. The QOL of hypertensive patients tends to be worse among those with co-morbidity [810]. In Vietnam, a number of studies have examined QOL among older people; and people living with HIV and AIDS [1114].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this definition, literature shows a lower QOL among overweight individuals with CNCD considering that these complications can increase the limitations of individual daily activities, reduced vision, limb amputation, headache, anxiety, sleep disorders, joint pain, difficulty breathing, muscle and bone problems and low self-esteem (4) .…”
Section: Introductionmentioning
confidence: 99%